Influence of the installation configuration of heat exchangers on the operation of a heat pump assisted dryer (Research, Society and Development, 2021)
A prototype of a dryer with a small capacity heat pump was developed and assembled in the laboratory, for drying thermosensitive products, with a refrigeration system coupled to a thermally insulated chamber, fixed to a single structure. Two options for mounting the heat exchange system inside the drying chamber were tested. In the first option (configuration 1), a configuration with a single heat exchanger was used, which alternated the function of evaporator and condenser, in cooling and heating cycles, through the use of a four-way valve. In the second option (configuration 2), a configuration with two heat exchangers was used, where the air passed first through the evaporator and then through the condenser. The settings were evaluated according to the psychrometric operating conditions: temperature, relative humidity and equilibrium air humidity. Configuration 2 was more effective in conditioning the drying air, with more favorable psychrometric conditions, resulting in lower average equilibrium moisture values.